Electrical behaviour of zirconium doped calcium copper titanium oxide - Parkash O.; Kumar D.; Goyal A.; Agrawal A.; Mukherjee A.; Singh S.; Singh P. (My University, 2025)
In this investigation, the effect of Zr substitution at the Ti site of the CaCu3Ti4O12 on the electrical properties has been studied. Samples with composition x = 0.00, 0.10 and 0.30 have been synthesized by the solid state ceramic route in the system CaCu 3Ti4-xZrxO12. Powder x-ray diffraction data showed the formation of a single phase solid solution. The structure remains cubic similar to an undoped sample. The Seebeck coefficient, α, is measured on a thick pellet in the temperature range 500-800 K and is found to be negative in this temperature range, indicating n-type conduction in the temperature range of measurement. Dc resistivity, ρdc, and ac conductivity, σac, were measured to understand the mechanism of conduction. Immittance analysis is used to separate the contributions of the grains and grain boundaries to the total observed resistance. From the temperature and frequency dependence of ac conductivity, it is concluded that at and around room temperature conduction occurs due to thermally activated rotation of dipoles while at high temperature it occurs due to excitation of charge carriers at the conduction band edge and hopping at energies close to it. From the immittance analysis it is observed that activation energies of conduction for grains and grain boundaries are almost equal indicating the same mechanism of conduction. © 2008 IOP Publishing Ltd.